Postharvest Hexanal Application Delays Pericarp Browning Under Cold Storage in Litchi Fruit - Muhammad Shafique; Butt, Madiha; Masroor, Ashir; Khan, Muhammad Yahya; khanum, Plosha; Waqas, Muhammad Rashid (Journal of Agriculture and Biology, 2025)
Litchi is the fruit of warm climates and has a very short shelf life as the fruit loses its red color within the span of 2-3 days. The current study was planned to evaluate the effect of hexanal fumigation on overall fruit quality and retention of aesthetic appeal of the fruit under low temperature storage conditions. Hence, litchi fruit harvested at the ripening stage was fumigated with 0%, 1%, 2%, 3%, and 4% hexanal concentration followed by cold storage at 5 ± 1°C for 28 days by maintaining 90% relative humidity. During cold storage, fruits were evaluated for physiological weight loss (PLW), browning severity, and anthocyanin depletion in pericarp. Physico-chemical quality characteristics were determined in litchi aril samples. Total phenolics and total antioxidants were also determined from aril samples, whereas antioxidative enzymes such as SOD, CAT, POD PPO were determined from pericarp tissues in litchi pericarp at 7 -day intervals. Postharvest hexanal application significantly controlled pericarp browning and resulted in higher anthocyanin content with reduced weight loss than control fruit. Hexanal preserved a steep rise in SSC and maintained relatively low SSC compared to control fruit throughout the cold storage period; however, titratable acidity, ascorbic acid contents, phenolic components and total antioxidants in litchi fruit aril were significantly augmented in all hexanal formulations, with significantly higher values recorded in 1% hexanal treatment. Likewise, antioxidative enzyme activities, such as SOD (74.54 mg-1 protein) and CAT (82.42 mg-1 protein), were significantly higher in hexanal-treated fruits, while POD (30.2 mg-1 protein) and PPO enzyme (34.42 U mg-1 protein) activities were significantly hindered in hexanal-treated litchi fruits which were significantly higher in control treatment. Overall, 1% hexanal formulation showed more promising results in terms of maintaining quality characteristics and color of the fruit during the extended storage period. Conclusively, hexanal application retained the pericarp red color and delayed browning by maintaining fruit quality of ‘Gola’ litchi longer than control fruits.
Keywords: Antioxidative Enzymes; Pericarp Browning; Physico-chemical Quality